Sustainable Modernity : The Nordic Model and Beyond. - Witoszek, Nina. (Routledge Studies in Sustainability Series, 2018)
Contributors provide insights from the humanities, the social sciences, and the latest developments in evolutionary science to cast new light onto how the Nordic countries have forged sustainable, inclusive, and productive communities.